Pengaruh Financial Literacy dan Financial Attitude Terhadap Financial Management Behavior dengan Mediasi Locus of Control - Pricilla, Ani; Yusuf, Muhammad; Handarini, Dwi (LPPM Universitas Negeri Jakarta, 2024)
This study aims to test and analyze the effect of Financial Literacy and Financial Attitude on Financial Management Behavior mediated by Locus of Control. Quantitative methods are used with non-probability sampling using purposive sample techniques. The research primary data was collected through a questionnaire obtained from a total sample of 71 students of the Bachelor of Accounting, State University of Jakarta and processed using the PLS-SEM technique with SmartPLS 4.0. The results concluded that Financial Literacy and Financial Attitude significantly have a positive effect on Financial Management Behavior. In addition, both variables significantly have a positive effect on Financial Management Behavior through mediated by Locus of Control. This study provides a theoretical contribution to the Theory of Planned Behavior and contributes implications for students, especially in Bachelor of Accounting as one of the graduate competencies is as a financial analyst who needs to have good financial management behavior skills.